1959
DOI: 10.1111/j.1474-919x.1959.tb02395.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration Across the Sea

Abstract: Summary. Small passerine species regularly migrate across at least 600 miles of sea, and some take longer journeys, notably the Greenland Wheatear. Disputes concerning the crossing of the Gulf of Mexico, Mediterranean and North Sea are summarized. Pre‐migratory fat seems enough for a continuous Bight of 24–36 hours and perhaps more. Most of it is lost after drift.3. Diurnal migrants tend to coast into the wind before setting out to sea, especially in weather rather unfavourable for migration. Their following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The migrations of Norwegian, Swedish and Finnish thrushes have been described by Rendahl (1960, 1961), Kruger (1940), Holgersen (1953) and Ashmole (1962). Lack (1959). He concluded that Redwings, Blackbirds and Fieldfares almost certainly make a direct passage over the North Sea quite regularly, and analysis of ringing recoveries has supported this view (Goodacre 1959, Ashmole 1962).…”
Section: The Migration Of Thrushes From Scandinaviamentioning
confidence: 99%
“…The migrations of Norwegian, Swedish and Finnish thrushes have been described by Rendahl (1960, 1961), Kruger (1940), Holgersen (1953) and Ashmole (1962). Lack (1959). He concluded that Redwings, Blackbirds and Fieldfares almost certainly make a direct passage over the North Sea quite regularly, and analysis of ringing recoveries has supported this view (Goodacre 1959, Ashmole 1962).…”
Section: The Migration Of Thrushes From Scandinaviamentioning
confidence: 99%
“…The first attempts to quantify nocturnal bird migration were made with short‐range X‐band scanning radar (Eastwood , Drake and Bruderer ). In many countries, military and civil air traffic radar is used to study the spatial and temporal distribution of bird migration on a larger, often national scale (Sutter , Lack , Alerstam , Buurma , Ruhe 2000). However, continent‐wide studies have only become possible via the use of data from WSRs.…”
Section: Animal Distribution Numbers and Biomass In Time And Spacementioning
confidence: 99%
“…With the introduction of radar by the military during the Second World War it soon became obvious that radar could help fill gaps in our understanding of how flying animals use the airspace (Brooks 1945, Lack and Varley 1945, Buss 1946, Sutter 1957, Eastwood 1967. Since that time, many different types of radar (Table 1) have been broadly applied to study the 'invisible parts' of the movements of both birds and insects on a broader scale, primarily in Europe, North America, east Asia and Australia (Lack 1959, Drury and Keith 1962, Alerstam 1972, Myres and Apps 1973, Williams and Ying 1990, Bruderer 1997a, b, 2003, Drake and Reynolds 2012, Beason et al 2013, Drake and Bruderer 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of the above winter visitors arrive on the east coast of England (East Anglia to Kent) on a broad front direct from Germany or the Low Countries, while others arrive direct from Scandinavia in smaller numbers sometimes as a result of westward drift during movements not normally touching the British Isles. Lack (1959Lack ( b, 1963 considers that some Norwegian Starlings may coast round the eastern side of the Xorth Sea and make the shorter crossings from Holland or Cap Gris Sez, and this appears to be usual for Chaffinches Fringilla coelebs. There is also evidence that some Starlings move as far as the Cherbourg peninsula before turning north to arrive in southern and southwestern Britain.…”
Section: Origiks Of Outbreakbmentioning
confidence: 99%
“…Even so, visual observations in East Anglia and Kent show that most Starlings arriving from the sea do not alight in the immediate coastal belt. Lack (1960) was able to measure the speed of migrating Starling flocks and obtained a mean air-speed over several mornings of 37 knots. This figure agrees with the speed of Starling flocks timed over the three miles between the South Goodwin lightship and the cliffs at St. Margaret's Bay (Min.…”
Section: Origiks Of Outbreakbmentioning
confidence: 99%